Analisis Peran Etika dan Profesionalisme Polisi Sebagai Penegak Hukum Dalam Menjaga Kepercayaan Masyarakat: Studi Kasus Ferdy Sambo - Widiyanto, Alif Putra; Febriani, Anggie; Julio, Christopher Elia; Rahmawati, Dian Istimeisyah; Nandita, Lufna; Friyadhi, Naufal Farros; Tanjung, Salsas Bila Juniyanti; M, Mulyadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the role of ethics and professionalism of the police as law enforcers in maintaining public trust, with a case study of ethical and legal violations committed by Ferdy Sambo. This case highlights the gap between public expectations of the integrity of the police and the reality of practices in the field, which has an impact on the crisis of public trust in the police institution. The study uses a descriptive qualitative method through literature studies and data analysis from various news sources and related literature. The findings show that violations of the code of ethics and abuse of power by officers, especially in the case of Ferdy Sambo, worsen the image and legitimacy of the police institution. The failure of the internal monitoring system and the weak implementation of sanctions for ethical violations are the main factors in the decline in public trust. This study emphasizes the importance of implementing the principles of integrity, justice, and responsibility as stipulated in Law No. 2 of 2002 and Regulation of the Chief of Police No. 14 of 2011. This study also provides strategic recommendations to strengthen the monitoring system and enforcement of the code of ethics in order to restore public trust. Thus, improving ethics and professionalism within the police force is key to restoring the legitimacy and public trust in the police institution in Indonesia.